The Influence of Inhomogeneity Present in Layered Biological Structure on Electromagnetic Field Distribution - Katarina Istenikova (Communications - Scientific letters of the University of Zilina, 2011)
The knowledge of electrical properties of biological materials and their interaction with electromagnetic waves is necessary for suitable determining the effect of electromagnetic field on biological systems and, sequentially, prevention of undesirable consequences on human organism. Because of complex heterogeneous structure of human body the electromagnetic field distribution in biological systems is very complicated and depends, among others, on the type of tissue and on the presence of complicated layered structures and interfaces. With the knowledge of these electrical properties the absorption of energy and the field distribution which are the results of the solution to a boundary value problem can be obtained. This paper is focused on description of influence of inhomogeneity occurring in the human structure on electromagnetic field propagation. The inhomogeneity is represented by silicon brick and brain tumor placed into the model.